Late Quaternary Evolution of a Submerged Karst Basin Influenced by Active Tectonics (Koločep Bay, Croatia) - Dragana Šolaja; Slobodan Miko; Dea Brunović; Nikolina Ilijanić; Ozren Hasan; George Papatheodorou; Maria Geraga; Tatjana Durn; Dimitris Christodoulou; Ivan Razum (Journal of Marine Science and Engineering, 2022)
Koločep bay is a 30 km elongated karst basin located between the Elafiti Islands and the mainland with a NW–SE general direction. The bay lies within the seismically active southern Dalmatia zone. Irregular grid sub-bottom profiles and two legacy reflection seismic profiles have been used to determine the overall morphology of the bay and to establish the seismic stratigraphy of its sedimentary infill. Three major seismic–stratigraphic units have been identified in the upper ~50 m of the ~120-meter-thick sedimentary sequence that lies above the karstified limestone bedrock. The karst polje basin was flooded due to sea-level rise before 12.1 kyr BP. The morphology of the bay implies complex influences of Late Glacial meltwater discharges, aeolian sand deposition, the existence of paleo–ponor/karst spring zones and buried Pleistocene river channels. The Pleistocene seismotectonic units are deformed in the NW and SE parts of the basin. The central part of the basin has no signatures of intensive tectonic activity during the Holocene. A major erosion event was identified that led to the formation of a basin within the older sedimentary infill. In the southern part of the basin, we have evidence of Holocene tectonic activity with the formation of erosional scarps on the seafloor of the bay.